Examining the Forms of Central Government’s Dominance over Local Governments in Liberia - Nyeleker, Kerkulah P; Prasetyo, Satria Iman (ARISTO, 2024)
In recent years, the government of Liberia and its stakeholders have developed several policies towards decentralization that have led to significant developments. However, challenges still remain, especially the dominance of the central government, political greed, etc. This study aims to identify the forms of central government’s dominance over local governments in Liberia and its impacts on local governance. This research applied a qualitative method with primary data obtained through interviews with relevant informants and secondary data obtained through analysis of previous studies, mass media, and policies regarding decentralization in Liberia, and analyzed using an interactive model in addition to the NVivo 12 Plus software. The findings reveal that the central government exerts dominance in three forms, including visible, hidden, and invisible forms. Visible forms include explicit regulations predominantly financial control and local officials' appointment, which allowed the central government to dictate local governance. Hidden forms mainly include intimidation and political party influence, which are not publicly acknowledged, allowing the central government to maintain its dominance and often devaluing local agendas. Invisible forms mainly include institutional capture and policy development, shaping the mindsets of local officials and citizens as well as viewing this dominance as natural, thus leading to a culture of silence. Hence, the research emphasizes the need for further reforms to ensure a balanced distribution of power and the independence of local governments to serve communities effectively and make decisions aligned with local needs.